Cytotoxic agents from luvunga scandens human breast adenocarcinoma cell line (MCF-7) - Al Zikri, Putri Nurhidayah; Arief Ichwan, Solachuddin Jauhari; Darnis, Deny Susanti; Bakhtiar, M. Taher (2014)
Breast cancer is among of the frequently diagnosed cancer and causes high mortality rate in most countries in the world. These led to the necessity for the development of potential chemotherapeutic agents against breast cancer cells with novel mechanisms of actions. The plant-derived triterpenoids commonly used due to its ability to exhibit cytotoxicity against a variety of tumor cells. Luvunga scandens (Rutaceae) is one of the plants that contain triterpenoids. L. scandens was extracted and assayed on human breast adenocarcinoma cell line (MCF-7). The stems of L. scandens were extracted with n-hexane, dichloromethane (DCM) and ethanol (EtOH). DCM extracts were then further fractionated by vacuum liquid chromatography (VLC) into five extracts; namely n-hexane, n-hexane:DCM, DCM, DCM:MeOH and MeOH. Those five extracts were assayed in vitro cytototoxic activity against MCF-7. Among them, DCM:MeOH fraction was found to be the most effective and was further subjected to isolation procedure and the isolated compound was assayed in vitro cytotoxic activity against MCF-7. Bioactivity-guided fractionation of the fraction through successive column chromatography procedures led to the isolation of a triterpene-type of compounds. The structure of the compound was elucidated to be lanosta-8, 24-dien-21-oicacid, 3-oxo, (13a, 14b, 17a, 20S) with molecular formula of C3OH46O3. This compound was found to be responsible for the cytotoxicity effects with the IC50 value of 24.8 μM. Whereas IC50 of DCM extract and DCM:MeOH fraction extract is 75 and 94 μg/ml respectively. Therefore, it revealed that L. scandens is potential sources of cytotoxic agents.